Penyempurnaan instrumen input untuk akreditasi institusi pendidikan tenaga kesehatan di Propinsi Jawa Tengah = Refinement of input instrument for accreditation at the educational institution for health workers centreJava - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Background: The purposes of this research were: ( I ) to design an input instrument for quality study at the Educational Institution for Health Workers